Extension of Objects Eligible for Industrial Property Right Protection as Inventions in Vietnam - Quoc Nguyen, Phan (VNU Journal of Science: Legal Studies; Vol 38 No 1, 2022)
Vietnamese law on intellectual property in general and industrial property rights protection as inventions in particular stipulate the patentable subject matters that are considered suitable with the international laws. However, to increase the patent filing number and promote the protection and exploitation of patent, the list of ineligible objects for industrial property rights protection as inventions needs to be shorter. The article analyses some international experience in extending the objects.